Nasal colonization of methicillin resistant Staphylococcus aureus in Ethiopia: a systematic review and meta-analysis - Alemayehu Reta; Abeba Mengist; Asnakew Tesfahun (BMC, 2019)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) is one of a medically important Gram-positive bacteria, which can be harboured majorly in the nasal cavity. Risk of consequent infection in a person colonized with S. aureus as well as MRSA upsurges with time and remains insistently increased. Hence, the objective of this meta-analysis was to determine the prevalence of S. aureus and MRSA nasal colonization in Ethiopia at large. Methods PubMed, Google Scholar, Embase, Hinari, Sci Hub, Scopus, and the Directory of Open Access Journals were searched and a total of 10 studies have been selected for meta-analysis. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used for the literature search strategy, selection of publications, data extraction, and the reporting of results for the review. All statistical analyses were performed using STATA version 11 software via random effects model. The pooled prevalence was presented in forest plots and figure with 95% CI. Results A total of ten studies with 2495 nasal swab samples were included in this meta-analysis, and the overall pooled estimated prevalence of S. aureus and MRSA nasal colonization in Ethiopia were 30.90% [95% CI 21.81-39.99%], 10.94% [95% CI 8.13-13.75%] respectively. Subgroup analysis was also noted in different regions of Ethiopia, henceforth Oromia region ranked first 21.28% [95% CI 8.22-34.35%], followed by Amhara region 6.78% [95% CI 3.02-10.54%], whereas relatively low magnitude of MRSA colonization was demonstrated from Tigray region 4.82% [95% CI 2.18-7.45%]. Conclusion The analysis showed that the overall prevalence of S. aureus and MRSA nasal colonization in Ethiopia were comparable with the global prevalence. But a huge variation between the regions, so the Ministry of Health of Ethiopia should design appropriate decolonization program that can address the specific regional groups as well as the national population.